A cross-scale hygro-mechanical coupling model for hollow glass bead/resin composite materials. (1st March 2023) - Wang, Jingze; Cui, Weicheng
Highlights: We proposed a hygro-mechanical coupling model for HBG/resin composites. We studied the distributions of stress and diffusion coefficient. We gave the relationship between the deviation and the water absorption. Abstract: Hollow glass bead/resin composite materials are now mainly used in the deep sea submersibles. They are also targeted for application in aviation, aerospace and military applications in the future because of their good material properties, such as low density and high compressive strength. However, there is a coupling relationship between the stress and hygroscopicity in their water absorption process. This reduce the safety of structures produced by hollow glass bead/resin composite materials, especially the underwater and deep-sea structures. In this paper, a hygro-mechanical coupling model and its simplified model for hollow glass bead/resin composites are proposed based on Fick's second law. A number of experiments are conducted to validate these two models. Comparisons of the predictions of these two models with experimental data show good agreement. The distribution and variation of the stress, water absorption and diffusion coefficient of the composite during the water absorption process were studied. The relationship between the deviation and the water absorption in the simplified model has been given. These results can guide the engineering application of hollow glass bead/resin composite materials, especially in deep sea environments.